On national and international trade in greenhouse gas emission permits - Katrin Rehdanz; Richard S. J. Tol (Fondazione Eni Enrico Mattei (FEEM), 2002)
This paper considers the question under what conditions domestic markets of emission permits would and should merge to become an international market. Emission permits are licenses, and so governments would need to recognize other countries' permits. In a two-county model, we find that it is in both countries' interests to form an international market, and it may even be beneficial to the environment. Three different policy instruments of the importing country are examined, namely a price instrument (tariff) and two quantity instruments (discount and import quota). All instruments restrict trade. The importing country (and regulator) prefers an import tariff and an import quota to a carbon discount. If the exporting country releases additional permits, the importing country should not try to keep total emissions constant, as that would be ineffective if not counterproductive. Instead, the importing country should aim to keep the total import constant; this would impose costs on the exporting country that are independent of the policy instrument; an import quota would be the cheapest option for the importing country. Compliance and liability issues constrain the market further. However, both the importing and the exporting country would prefer that the permit seller is liable in case of non-compliance, as sellers' liability would less constrain the market.
Keywords: Q25; Q28; 330; Emissions trading; Environmental policy; Liability and compliance; Climate change; Emissionsrechte; Luftverunreinigung; Zwei-Länder-Modell; Außenhandelsbeschränkung; Theorie